PENGARUH KEPEMILIKAN PENGENDALI, PROPORSI KOMISARIS INDEPENDEN, DAN KOMITE AUDIT TERHADAP AGRESIVITAS PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI: (Studi Kasus Pada Perusahaan Sektor Energi di Bursa Efek Indonesia Tahun 2017 - 2021) - Fitria Ningrum, Ayu; Napisah, Napisah (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
This study aims to determine the effect of controlling ownership, the proportion of independent commissioners and audit committees on tax aggressiveness with company size as moderator. The method used in this research is quantitative. The population of this study are energy sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period with a total of 37 companies and after following the sample criteria, there are 13 companies. The type of research used is quantitative research using Panel Data Regression and Moderated Regression Analysis (MRA) using Microsoft Excel and EVIEWS version 10. The data analysis technique used is Descriptive Statistical Analysis, Panel Data Regression Model Estimation, Classical Assumptions Test, Hypothesis Testing , and Moderating Regression Analysis (MRA) Test. Based on the results of the Coefficient of Determination Test (R2), the influence exerted by the independent variables on the dependent variable in this study was 3% and the remaining 97% was influenced by other variables not included in this study. The results of the T-Test show that Ownership of the Controller has no effect on Tax Aggressiveness, the Proportion of Independent Commissioners has no effect on Tax Aggressiveness, the Audit Committee has no effect on Tax Aggressiveness. The results of the Moderating Regression Analysis (MRA) test show that Company Size moderates Controlling Ownership of Tax Aggressiveness, Company Size cannot moderate the Proportion of Independent Commissioners on Tax Aggressiveness, Company Size can moderate the Audit Committee on Tax Aggressiveness